Partially Melted Crustal Xenoliths as a Window into Sub-Volcanic Processes: Evidence from the Neogene Magmatic Province of the Betic Cordillera, SE Spain - Alvarez-Valero, A; Waters, D (2010)
Crustal xenoliths from the NeogeneVolcanic Province (NVP) of the Betic Cordillera, SE Spain, constitute an unusual suite of high-grade melt-bearing metapelitic rocks derived in two stages from metasediments surrounding crustal magma chambers. Microstructures and age relationships indicate that a first stage of migmatization and melt extraction was overprinted by a sequence of melt-bearing reaction microstructures. The preservation of melt as glass requires only a short residence time before eruption of the xenoliths in the host melt. The P-T conditions of the melting processes have been constrained by metamorphic modelling of mineral assemblages, phase compositions and reaction sequences in local compositional domains in the system NCKFMASHTO using THERMOCALC software. The calculations predict that within the El Hoyazo and Mazarrón volcanic suites, Grt-Bt-Sil (± Crd, Pl) enclaves containing a distinctive fibrolite-melt intergrowth formed over the temperature range 700-770°C at 5 kbar, and that these were overprinted by corona structures around garnet containing Spl-Crd-Kfs-melt at 775°C, 4·8 kbar, and newly grown spinel with melt haloes (only at El Hoyazo) at 835°C and 5·8 kbar. At Mar Menor, the xenoliths show garnet replaced by Opx, Crd, Spl and melt at 810-840°C, 2-2·5 kbar; aluminous xenoliths containing andalusite were replaced by Spl + Crd under the same conditions.The P-T distribution, size and relative abundance of the various xenolith types are best explained by the formation of the melt-bearing assemblages in a transiently heated wall-rock profile adjacent to a magma chamber or conduit, followed by collapse of the wall and brief residence of the resulting fragments as xenoliths in a dacitic magma at c. 850°C. The difference in pressure between the locations reflects the depth of magma chambers in the crust.The predominance of smaller, hotter enclaves in the Mar Menor occurrence may reflect less favourable conditions for developing thermally softened wall-rock profiles along high thermal radients at shallower depth. © The Author 2010.